2012
DOI: 10.1186/1472-6874-12-43
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and the influence of culture: another gap for Indigenous Australian women?

Abstract: BackgroundThere is great variation in experience of menopause in women around the world. The purpose of this study was to review current understanding of Australian Aboriginal and Torres Strait Islander (Indigenous) women’s experiences of menopause. The literature pertaining to the perception, significance and experience of menopause from a number of cultural groups around the world has been included to provide context for why Indigenous women’s experience might be important for their health and differ from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 40 publications
1
30
0
3
Order By: Relevance
“…Besides, they experience more physiological problems than males. One of these problems is menopausal transition (MT) (2). During MT, a female moves from her reproductive age towards menopause (3).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Besides, they experience more physiological problems than males. One of these problems is menopausal transition (MT) (2). During MT, a female moves from her reproductive age towards menopause (3).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study from Iran showed that 59.8% of middleaged females suffered from overweightness and obesity (2). Another study revealed that menopausal females consumed limited amounts of calcium and dairy products (7).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations